Enhancing enzymatic stability of bioactive papers by implanting enzyme-immobilized mesoporous silica nanorods into paper - Zhao, Z.; Tian, J.; Wu, Z.; Liu, Jian; Zhao, D.; Shen, W.; He, L. (R S C Publications, 2013)
Enzyme horseradish peroxidase was immobilized on mesoporous silica nanorods to fabricate enzymatic bioactive papers with increased bio-stability. The new bioactive papers based on the immobilized enzyme have tremendously high stability both at room temperature and at 37 °C, in contrast to the low stability of conventional bioactive papers using free enzymes.